2003
DOI: 10.1007/s11661-003-0307-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N addition on tensile and corrosion behaviors of CD4MCU cast duplex stainless steels

Abstract: The effect of N addition on the microstructure, tensile, and corrosion behaviors of CD4MCU (Fe-25Cr-5Ni-2.8Cu-2Mo) cast duplex stainless steel was examined in the present study. The slow strain rate tests were also conducted at a nominal strain rate of 1 ϫ 10 Ϫ6 /s in air and 3.5 pct NaCl ϩ 5 pct H 2 SO 4 solution for studying the stress corrosion cracking (SCC) behavior. It was observed that the volume fraction of austenitic phase in CD4MCU alloy varied from 38 to 59 pct with increasing nitrogen content from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…4. The resistance to SCC in 3.5 pct NaCl ϩ 5 pct H 2 SO 4 for CD4MCU alloys with different Cr contents showed a similar trend as observed in the polarization and the potentiostatic test results. Unlike the general corrosion test results, however, the SCC resistance of CD4MCU23 alloy was substantially greater than that of CD4MCU28 alloy due to the break down of stable passive film during tensile deformation.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…4. The resistance to SCC in 3.5 pct NaCl ϩ 5 pct H 2 SO 4 for CD4MCU alloys with different Cr contents showed a similar trend as observed in the polarization and the potentiostatic test results. Unlike the general corrosion test results, however, the SCC resistance of CD4MCU23 alloy was substantially greater than that of CD4MCU28 alloy due to the break down of stable passive film during tensile deformation.…”
Section: Discussionsupporting
confidence: 74%
“…Our previous studies on the effect of N on the microstructural evolution of CD4MCU cast duplex stainless steel suggest that the globulization of austenitic phase is strongly related to the N content in the ferrite matrix. [4,7] The presence of Cr in the ferrite matrix is reported to increase the N solubility in the ferrite matrix, and the increased N content in the ferrite would encourage the globulization of austenitic phase. However, further studies are required to confirm this notion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, DSS is replacing conventional austenitic or ferritic stainless steels in many industrial applications because of its combined advantages of better mechanical and corrosion properties. [1][2][3][4][5] DSS contains austenite stabilizing elements like Ni, Mn, C, N and Cu as well as ferrite stabilizing elements like Cr, Mo and Si. The recent skyrocketing raw material cost stimulates development of the DSSs with less alloying.…”
Section: Introductionmentioning
confidence: 99%
“…Since the development of first-generation duplex stainless steels in the 1930s, considerable research efforts have been conducted to improve both mechanical and corrosion properties, particularly by controlling alloying elements, such as N, Cr, and Mo [3,[6][7][8][9][10][11][12][13][14][15][16]. Charles [4], for example, reported that the addition of Cr and/or Mo improved the resistance to pitting corrosion and stress corrosion cracking of duplex stainless steels.…”
Section: Introductionmentioning
confidence: 99%